The Regionalism of Borders in Indonesia (Case Study: Sebatik Island, Indonesia) - Nugroho, Agung Satriyo; Rijanta, R; Santoso, Purwo; Marfai, Muh Aris (Faculty of Geography, Universitas Gadjah Mada, 2023)
Border management has, on the one hand, grown beyond the conceptual limit that is the terminological deﬁnition of borders as lines separating countries to also factor in their development as areas. On the other, it should aim to strengthen state sovereignty and improve the welfare of its citizens. Tese ofen lead to the dichotomy between security and prosperity in border management approaches. Regionalism is an approach used to create regional integration across national borders, but this concept is strongly inﬂuenced by the interests of states on each side of the border. Terefore, this research explores if spatial interaction between border communities is controlled by the regionalism concept introduced by the state or, instead, grows organically as part of regionalization due to livelihoods that require border crossings. It used a case study of Sebatik Island in the Indonesia-Malaysia border area. Te qualitative research design applied exploratory principles on the spatial interaction pattern formed between border communities and then synthesized the identiﬁed units of information on transboundary activities while considering government-issued policies on border management. Results showed that regionalism was only minimally implemented in managing the border area. It means that border landscapes in Indonesia are organically formed on the micro-scale even though the perspective of regionalism has long been adopted at the regional level, i.e., ASEAN.